The 2.6 Å Crystal Structure of a Human A(2A) Adenosine Receptor Bound to an Antagonist - Jaakola, Veli-Pekka (2008)
The adenosine class of G protein-coupled receptors mediates the important role of extracellular adenosine in many physiological processes and is antagonized by caffeine. We have determined the crystal structure of the human A(2A) adenosine receptor in complex with a high affinity subtype-selective antagonist, ZM241385, to 2.6 Å resolution. Four disulfide bridges in the extracellular domain combined with a subtle repacking of the transmembrane helices relative to the adrenergic and rhodopsin receptor structures defines a pocket distinct from that of other structurally determined GPCRs. The arrangement allows for the binding of the antagonist in an extended conformation perpendicular to the membrane plane. The binding site highlights an integral role for the extracellular loops, together with the helical core in ligand recognition by this class of GPCRs, and suggests a role for ZM241385 in restricting the movement of a tryptophan residue important in the activation mechanism of the class A receptors.